Anti-libidinal Interventions and Human Rights. (10th February 2021) - Forsberg, Lisa
Abstract: Anti-libidinal interventions (ALIs) are used in several jurisdictions to reduce male sex offenders' libido. One common objection to these interventions holds that when offenders are either required to undergo them or offered to undergo them as an alternative to continued incarceration, ALIs violate recipients' human rights. In this article, I examine this objection, which I call the human rights objection to ALIs, in relation to the European Convention on Human Rights (ECHR). Specifically, I examine the objection to ALIs in relation to Articles 3, 8 and 12 ECHR, which are the rights proponents of the human rights objection have identified as most relevant. I argue that the human rights objection in its current form fails to establish that ALIs violate recipients' ECHR rights in respect of all these Articles.